Enhanced photoelectric conversion efficiency of dye sensitized solar cells via the incorporation of one dimensional luminescent BaWO4:Eu3+ nanowires. Issue 74 (23rd August 2016) - Wang, Yuping; Qu, Yang; Pan, Kai; Wang, Guofeng; Li, Yadong
Abstract : One dimensional hierarchical BaWO4 :Eu 3+ nanowires have been prepared via a hydrothermal method for the first time. Abstract : One dimensional hierarchical BaWO4 :Eu 3+ nanowires have been prepared via a hydrothermal method for the first time. The obtained BaWO4 :Eu 3+ nanowires are not only a promising down-conversion luminescence material, but also can be used to improve the efficiency of dye sensitized solar cells, resulting an efficiency of 7.66%, which is a noticeable enhancement of 15% compared to the cell without BaWO4 :Eu 3+ nanowires. We suggest that the enhancement of the efficiencies of the TiO2 –BaWO4 :Eu 3+ composite cells was mainly related to the light scattering of BaWO4 :Eu 3+ .